PERANCANGAN VISUAL BRANDING SWEETTOOTH CAFE MELALUI MEDIA SHELF TV - VIVIKA SARI, Hendra Afriwan, S.Sn., M.Sn., San Ahdi, S.Sn., M.Sn (DEKAVE : Jurnal Desain Komunikasi Visual, 2014)
Sweettooth cafe is one of cafe in Padang. It was built on 31st September 2013 at Veteran street no. 74 F Padang. It is led by Dea Arnoli. Since it is built, sweettooth cafe uses social media and radio promotion. The needs of Sweettooth cafe now is how to make the consumen loyal.To achive that needs, the design of visual branding Sweettooth cafe trough shelf TV is made. Shelf TV is TV that’s is hang in shelf, it can be found in supermarket, café , airport. Shelf TV shows repeated video about a product. Because of that, shelf TV is used as the main media for branding Sweettooth cafe, the purpose is to increase consuments loyalty toward cafe and to gain Sweettooth cafe image. This design is supported by handbook, loyalty card, pin, cup, bookmark, CD cover, CD label, list of menu, sticker, and ID card.SWOT analysist is used as design method. SWOT is superiority, lack, chance, and risk in accompany. The power of Sweettooth cafe is combining cake and coffee. Besides, Sweettooth cafe girly concept has chance to be a relaxed place for carreer woman.Keywords : Visual Branding, Shelf TV, Sweettooth cafe